(untitled) (Olhar de Professor, 2020)
The following article has a goal to describe the process of elaboration of a book-game by a student with Attention Deficit Hyperactivity Disorder to study historical concepts. In a scenario of digital immersion, it is rather important the use of these resources in the scholar context for breaking of possible structural barriers in the educational system, beyond the rupture of the hierarchical structure and power relationships found in the educational system. For that, was developed a Study of Case with an eight-year-old child medically diagnosed with ADHD. The data were collected between April, May, and June of 2019, through a polling and the elaboration of a book-game inside the software Twine with a content chosen by the student. It was noticed that the obstacles found by the child during the realization of the activities at a regular class were transposed with the use of the book-game.